Pengaruh Fraksi Volume Serat Pinang dan Serat Rami Terhadap Sifat Fisis dan Mekanik Komposit Hibrid Sebagai Bahan Dasar Dashboard Mobil - Annisa, Hafizha Fitri; Mahyudin, Alimin (Universitas Andalas, 2025)
Research has been conducted on the effect of the volume fraction of jute fiber and areca nut fiber on the physical and mechanical properties of hybrid composites as a base material for car dashboards. This research aims to produce hybrid composites that have mechanical properties that are in accordance with the SNI of car dashboards and are environmentally friendly. The volume fraction of areca fiber and jute fiber is varied with a ratio of 1:1. The method of making samples using the hand lay-up method, which is a method of coating the fibers with the matrix manually. In this study, tensile strength, impact strength, density, and biodegradation tests were conducted. Based on the results of the study, the highest tensile strength value was at a volume fraction of 2% areca nut fiber and 2% jute fiber, namely 20.41 MPa. The highest impact strength value is in the volume fraction of 6% areca nut fiber and 6% jute fiber, which is 0.0206 J/mm^2. The highest density value was found in the volume fraction of 2% areca nut fiber and 2% jute fiber, namely 0.88 g/cm^3. The highest degradation rate was obtained in the volume fraction of 6% areca nut fiber and 6% jute fiber, namely 517%/day. From the research results, the optimum sample composition is in the variation of volume fraction of 2% areca fiber and 2% jute fiber.